Pastoral Counseling Approach in Overcoming Christian Family Problems at GMIT Maranatha Teunbaun - Riada, Marleny Rambu; Manubulu, Febriana Fransiska; Mangngi, Erick Apryan; Lasibey, Ferdinan S.E (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
Teunbaun is one of the places located in West Amarasi District, Kupang Regency, East Nusa Tenggara Province, where the majority of residents are Christian. The family as the smallest institution that builds a society is experiencing the biggest challenges along with developments over time, such as the emergence of problems or conflicts within the family, especially for married couples, causing arguments and domestic violence (KDRT) which will ultimately lead to infidelity or infidelity. divorce. Of course, these problems will psychologically affect a person's mental health because without realizing it, these various conditions have psychological effects such as anxiety disorders, depression, stress. This PKM activity was carried out with the aim of providing a good and correct understanding to married couples from the GMIT Maranata Teunbaun congregation regarding overcoming and managing problems within the family in the form of seminars and mentoring. The evaluation results show that the participants felt satisfied and had a good understanding of the seminar material presented and that the PKM activities met their expectations.